Working with proteins (Cogito Learning Media, 1997)
Discusses the challenge of growing protein crystals of high enough quality for structural analysis and shows how X-ray differentiation is used to collect crystal structure data at resolutions fine enough to discriminate individual atoms. Explains how computer analysis of diffraction data yields an image of the protein inside the crystal, known as an electron density map and how the process of atomic modeling provides a picture of the shape, secondary structure, and atomic details of the protein under investigation.